2016
DOI: 10.1089/cap.2015.0174
|View full text |Cite
|
Sign up to set email alerts
|

The Groundskeeper Gaming Platform as a Diagnostic Tool for Attention-Deficit/Hyperactivity Disorder: Sensitivity, Specificity, and Relation to Other Measures

Abstract: Objective: The purpose of this study was to assess the relative accuracies of the Conners' Brief Rating Scale, Parent Version, the Conners' Continuous Performance Test II (CPT II), and a novel interactive game called ''Groundskeeper'' to discriminate child psychiatric patients with and without attention-deficit/hyperactivity disorder (ADHD). Methods: We administered the three assessments to 113 clinically referred ADHD and non-ADHD patients who had been diagnosed with the Kiddie-Schedule of Affective Disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 36 publications
0
16
0
2
Order By: Relevance
“…Later, these authors replicated the study by replacing the previous predictive techniques with a logistic regression [ 20 ]. In this study, “Groundskeeper” achieved better results than both CPT and the Conners’ Brief Rating Scale.…”
Section: Bibliographic Reviewmentioning
confidence: 99%
“…Later, these authors replicated the study by replacing the previous predictive techniques with a logistic regression [ 20 ]. In this study, “Groundskeeper” achieved better results than both CPT and the Conners’ Brief Rating Scale.…”
Section: Bibliographic Reviewmentioning
confidence: 99%
“…In their study, virtual validity coefficients were quite high regarding participants’ past behaviors such as substance use and sexual patterns. Similarly, researchers have used choices with virtual characters to provide indicators that are diagnostic of problematic behaviors difficult to observe in real life (Faraone et al, 2016; Rizzo et al, 2000). For example, Faraone et al (2016) assessed ADHD children’s virtual behaviors (e.g., joint attention and attention seeking), finding that virtual behaviors may provide more effective diagnosis of ADHD than that of parental self-reports.…”
Section: Are Virtual Interactions and Choices Predictive Of Real-lifementioning
confidence: 99%
“…Similarly, researchers have used choices with virtual characters to provide indicators that are diagnostic of problematic behaviors difficult to observe in real life (Faraone et al, 2016; Rizzo et al, 2000). For example, Faraone et al (2016) assessed ADHD children’s virtual behaviors (e.g., joint attention and attention seeking), finding that virtual behaviors may provide more effective diagnosis of ADHD than that of parental self-reports. We should note that these coefficients between past and virtual behaviors were higher for behaviors that were not the target of behavior change, such as sexual position preferences, compared to those virtual choices involving behaviors that were also targeted (Godoy et al, 2013).…”
Section: Are Virtual Interactions and Choices Predictive Of Real-lifementioning
confidence: 99%
“…This review included other existing methods proposed to diagnose ADHD, that were not covered in the former systematic review. To make the indirect comparison possible, this in-house scoping review included only diagnostic accuracy studies that reported the chosen metrics of diagnostic for methods based on; electroencephalography and eventrelated potentials (Marcano et al, 2017;Loo et al, 2016;Snyder et al, 2015;Mohammadi et al, 2016;Gloss et al, 2016;Biederman et al, 2017;Gamma and Kara, 2016;Marcano et al, 2018;Manouilenko et al, 2017), structural and functional neuroimaging (Iannaccone et al, 2015;Rangarajan et al, 2014;de Celis Alonso et al, 2017;Qureshi et al, 2017;Serrallach et al, 2016;Hasaneen et al, 2017;Tan et al, 2017b;Uddin et al, 2017), simulated virtual reality and computer games (Negut et al, 2017(Negut et al, , 2016Berger et al, 2017;Faraone et al, 2016), and peripheral biochemical markers (Faraone et al, 2014;Scassellati and Bonvicini, 2015;Scassellati et al, 2012;Thome et al, 2012). According with this complementary "scoping review", the method presented in this research, seems to outperforms all the diagnostic accuracy metrics reported in the trials scrutinised in the aforementioned review.…”
Section: The Inferential Activity (Both At Sensory-motor and Represenmentioning
confidence: 99%